2003
DOI: 10.1038/sj.cdd.4401281
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking TNFα receptors 1 and 2 are resistant to death and fulminant liver injury induced by agonistic anti-Fas antibody

Abstract: The liver is particularly susceptible to Fas-mediated cytotoxicity. Mice given an adequate parenteral dose of agonistic antiFas antibody (aFas) or of FasL are known to develop a devastating liver injury and to die in a few hours. The present work shows that mice lacking TNFR1 and TNFR2 (R À ) both survive a single dose of aFas, otherwise rapidly lethal, and develop a mild form of hepatic damage, compared to the much more severe liver injury that in a few hours strikes wildtype mice (R þ ), eventually involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 52 publications
(73 reference statements)
3
33
0
1
Order By: Relevance
“…[43][44][45][46] In experimental systems, the administration of neutralizing antibodies to TNF has been shown to blunt the impact of inflammation on changes in transaminase levels. 40,42 Hepatic dysfunction due to the induction of high levels of inflammatory cytokines is consistent with the time course of these changes and the requirement for repetitive treatments. While all patients had elevated levels of inflammatory cytokines following treatment with Onyx-015, only one patient had significant increases in AST and ALT levels, suggesting that factors in addition to elevated cytokines levels contribute to the observed transaminitis.…”
Section: Minimal Hepatic Toxicity Of Onyx-015 T Au Et Alsupporting
confidence: 62%
See 1 more Smart Citation
“…[43][44][45][46] In experimental systems, the administration of neutralizing antibodies to TNF has been shown to blunt the impact of inflammation on changes in transaminase levels. 40,42 Hepatic dysfunction due to the induction of high levels of inflammatory cytokines is consistent with the time course of these changes and the requirement for repetitive treatments. While all patients had elevated levels of inflammatory cytokines following treatment with Onyx-015, only one patient had significant increases in AST and ALT levels, suggesting that factors in addition to elevated cytokines levels contribute to the observed transaminitis.…”
Section: Minimal Hepatic Toxicity Of Onyx-015 T Au Et Alsupporting
confidence: 62%
“…Transient increases in the levels of unconjugated bilirubin are seen during acute infections and are mediated by cytokines including TNF. [40][41][42][43][44] …”
Section: Minimal Hepatic Toxicity Of Onyx-015mentioning
confidence: 99%
“…Hepatocytes express large amounts of TNFR1 (17,18), and activation of this receptor by TNF␣ during inflammation can lead to hepatocyte apoptosis (19). However, TNFR1 can also be cleaved from the cell surface through proteolytic ectodomain shedding driven by activation of TNF␣-converting enzyme (TACE/ADAM17).…”
Section: Tumor Necrosis Factor (Tnf)mentioning
confidence: 99%
“…Another mechanism of Fas-associated liver damage and mortality elicited by Jo2 is TNF-a-mediated liver injury. Fas stimulation recruits neutrophils and activates Kupffer cells that secrete TNF-a, which aggravates Fas-mediated liver injury (Cazanave et al 2008;Costelli et al 2003;Mizuhara et al 1994;Matsuki et al 2002). On the other hand, Jodo et al reported that Jo2 delivers a Fas-mediated apoptosis signal to sinusoidal lining cells prior to hepatic parenchymal cells and this apoptosis signal is dependant on FccRII expression on sinusoidal lining cells.…”
Section: Discussionmentioning
confidence: 99%